0119 The Effect Of Sleep Continuity Disruption On Threat-related Attentional Bias: Randomised Controlled Experiment In Good Sleepers. (12th April 2019) - Reid, Matthew James; Omlin, Ximena; Notebaert, Lies; Espie, Colin; Kyle, Simon
Abstract: Introduction: Previous research indicates that attentional bias towards emotional stimuli may contribute to the development and maintenance of psychopathology. Moreover, experimental studies show that sleep loss impairs functioning in neural circuitry underpinning emotion perception and regulation, resulting in increased reactivity to negative emotional stimuli. We sought to test the hypothesis that sleep continuity disruption causally induces emotion-related attentional bias, providing a mechanism through which sleep disturbance confers risk for psychopathology. Methods: 51 healthy good sleepers (37 female; mean age = 24 years) were randomized to either one night (23:00-07:00) of undisturbed sleep (US) (n=24) or one night of sleep continuity disruption via forced awakenings (FA) (n=27). Participants in the Forced Awakening condition were awoken eight times, either for 20 mins (x6), 40 mins (x1) or 80 mins (x1) in a fixed pattern standardized across participants. A dot-probe task (Notebaert, Clarke & Macleod, 2016) was used to assess attention bias towards threat-related (versus neutral) words in the evening prior to and the morning following the sleep period. An attentional bias index score was computed for each participant, reflecting the extent to which participants showed preferential attentional allocation towards threat versus neutral words. A positive attentional bias index reflects a greater attentional bias towards threat-related stimuli. Results: Analyses of variance tested for a main effect of time (pre vs post sleep) and a group*time interaction. Results showed there was no effect of time [F = .068, p=.795; Mean pre = -.593 ms vs Mean post = -1.91 ms] or group*time interaction [F = .141, p=.709]. Conclusion: Sleep continuity disruption had no discernible effect on attention bias for threat-related words. Moreover, across both groups, there was no clear change in attention bias from pre-to-post sleep. Further work with different types of sleep manipulations is warranted. Support (If Any): N/A